The Influence of Avoidant Attachment to the Formation of Assertive Character in Early Childhood - Puji Astuti, Henny; Eka, R Agustinus Arum; Utami, Tri (Universitas Negeri Semarang, 2015)
The assertive character in early childhood is the way of thinking and behaving honest and open to express their needs, honest feelings and thoughts, struggling for individual rights, and rejecting unreasonable requests including pressure from authority figures and also from standards that apply to the group as his feature. Attachment avoidance is various of insecure attachment, where children choose to avoid from the presence of his parents. This study aims to get the facts of the effect of avoidant attachment to the establishment of the assertive character of early childhood. The hypothesis of this study is avoidant attachment have an influence on the establishment of the assertive character of early childhood. The experiment was conducted in the District Bergas, Semarang regency using 42 early childhood as subjects. The method of collecting data using assertive character Scale and Scale Avoidant Attachment, as well as data analysis using Simple Linear Regression using SPSS (Statistical Package for Social Science) 16 for Windows. The results of this study are avoidant attachment has influenced on the establishment of assertive character in early childhood.How to citeAstuti, H. K., Eka, R. A. A., Utami, T. (2015). The Influence of Avoidant Attachment to the Formation of Assertive Character in Early Childhood. Indonesian Journal of Early Childhood Education Studies, 4(2), 116-122. doi:10.15294/ijeces.v4i2.9466DOI 10.15294/ijeces.v4i2.9466